CT Scan as A Diagnostic Modality of Gastrointestinal Stromal Tumor: A Systematic Review - Mazni, Yarman; Robby, Rizky DK (UI Scholars Hub, 2018)
Introduction. Preoperative diagnosis of GIST is an important factor in the management. However, due to the rarity of the case, there is a controversy about the accuracy of CT scan as an accurate diagnostic tool. Therefore, a systematic review is required to find out the answer. Method. A review was conducted to find out evidence of the highest level regarding the accuracy of CT scan as a diagnostic modality of GIST. The study addressed to find out the sensitivity, specificity, positive and negative predictive values. A literature search carried out in database sites i.e. PubMed, ClinicalKey, ScienceDirect, and Cochrane using keywords “gastrointestinal stromal tumor” OR “GIST” AND “ultrasound” OR “CT scan” OR “MRI” AND “diagnostic” OR “imaging”. Systematic reviews, RCTs, cohort study, case report or series, studies in adults, published within the last ten years, and availability in full text were included. Correspondence, editorial, or commentary, and no histopathology data were excluded. The articles were critically appraised. The review proceeded in accordance with PRISMA. Results. Twelve studies were analyzed in the study. The sensitivity of CT scan was in range of 77.26–94.9%, specificity 77.2–100%, PPV 74.38– 100%, and NPV 68.32–81.2%. CT scan was found to be the modality of choice in establishing the diagnosis of GIST. Central necrosis, heterogenous enhancement, cavitation without lymphadenopathy were the features represented by CT scan. Conclusion. CT scan is the modality of choice in establishing diagnosis of uncomplicated GIST, with sensitivity and specificity of 94.9% and 100%, respectively. Other modalities were considered in advanced or GIST with metastasis.